PLATELET-RICH PLASMA FOR PERSISTENT ULCERS OF THE LOWER LIMBS - I. V. Gilevich; T. V. Fedorenko; E. A. Kolomiytseva; V. V. Fedyushkin; E. N. Shubrov; S. G. Slavinsky (Инновационная медицина Кубани, 2019)
Background. Estimation of safety and efficiency of platelet-rich plasma in complex treatment in patients with persistent large ulcers.Material and methods. Two clinical cases of patients with long persistent ulcers of the lower extremities that were administered local injections of the autologic platelet-rich plasma in the wound area in combination with or without autodermoplasty.Results. In the first case the patient had a trophic ulcer after erysipelatous inflammation without dynamics to healing in the setting of the carried treatment. Surgery was contraindicated due to severe accompanying pathology. This patient had 6 PRP courses (once a week). The regional epithelialization appeared on the 2nd week. After 6 injections full wound healing was noted. In the second case the patient had a long persistent post-traumatic ulcer with 2% square. The autodermoplasty with local introduction of PRP was performed. We observed a full graft acceptance on the 6th day.Conclusion. PRP use will allow to improve outcomes of treatment persistent ulcers of the lower extremities. It represents extremely important to continue work on PRP application due to an absence of complications and obvious contraindications in this method for carrying out comprehensive analysis.